‘n Kerk wat getuig is ‘n kerk wat leef (1) ‘n Bybels-teologiese perspektief op die missionêre karakter van die kerk - Dreyer, D. J. (Verbum et ecclesia, 2002)
A witnessing church is a living church (1) A biblical-theological perspective on the missionary character of the church. In this, the first of two articles, we focus on the identity of the church as it is revealed in the Old and New Testaments. Since the sixties of the previous century, it is widely accepted that mission is the essence of the church. The church was no longer seen as the institution which sends people into the world, but was no longer the one who is sent into the world. According to the Old Testament, Israel was elected to be God’s witness to the nations. In exile they recognised that Jahwe is not a national God, but God of the whole world. The four Gospels, Acts and the letters of Paul make it very clear that the church of Jesus Christ is either a missionary church or not a church at all. The church is, in all its activities per se an instrument in bringing God's kingdom to this world.